Austria supreme, if it so wishes (1684) : a strategy for European economic supremacy - Hörnigk, Philipp Wilhelm von, 1640-1714 (Economic ideas that built Europe., 2018)
Austria Supreme, if It So Wishes (1684) provides a scholarly introduction to the Austrian-German mercantilist classic Oesterreich über Alles Wann es Nur Will (1684) by Philipp Wilhelm von Hörnigk.